The use of a risk‐orientated approach in comprehensive assessment of natural and technogenic emergency situations in the Kashirsky Municipal District of the Voronezh Region, Russia - T. V. Ovchinnikova; N. D. Razinkov; P. S. Kuprienko; T. V. Ashikhmina; A. V. Shmygol; A. A. Pavlenko (Юг России: экология, развитие, 2021)
The article reviews methodological approaches to risk assessment based on a comprehensive analysis of the frequency of natural and technological hazards in the territory of the Kashirsky Municipal District of the Voronezh Region.Aim. The purpose of this article is to assess and calculate the risks of emergency situations, based on a comprehensive analysis of the frequency of occurrence of natural and technological hazards in the Kashirsky Municipal District of the Voronezh Region, Russia.Methods. The risk assessment methods employed were based on the combined characteristics of damage and frequency of occurrence of negative environmental or man‐caused processes or hazardous events. Events associated with certain losses or people impacted upon by dangers were considered as negative processes.Results. The Kashirsky Municipal District is exposed to high risks of flooding, wildfires, biological and social processes, hazards associated with certain housing and communal service regimes and transportation accidents. There are also hydraulic structures and potentially hazardous facilities which increase risks of property damage in the area.Conclusion. It is necessary to reduce the level of social risk by carrying out preventive activities aimed at minimizing casualties. All scheduled maintenance requirements should be complied with in order to prevent a rise of risk of accident in life sustaining systems and infrastructures. The development of governmental departmental emergency monitoring systems, quarantine procedures and timely observational measures are recommended with the objective of reducing potential biological and social emergencies.